2022
DOI: 10.1155/2022/3378035
|View full text |Cite
|
Sign up to set email alerts
|

Circulating MMP-12 as Potential Biomarker in Evaluating Disease Severity and Efficacy of Sublingual Immunotherapy in Allergic Rhinitis

Abstract: Background. Allergic rhinitis (AR) is a highly heterogeneous disease, and allergen-specific immunotherapy (AIT) is an effective treatment. This study aims to evaluate the circulating mas-related G protein-coupled receptor-X2 (MRGPRX2) and matrix metalloproteinase-12 (MMP-12) levels in evaluating disease severity and predicting efficacy of SLIT in AR patients. Methods. We enrolled 110 moderate-severe persist AR patients (AR group) and 40 healthy controls (HC group). Circulating levels of MRGPRX2 and MMP-12 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…All three of these genes have known associations with allergen‐activated type 2 inflammation, including eosinophils, type 2 cytokines, and T helper 2 (Th2) cells. Variable expression of CLC and circulating levels of MMP‐12 have been suggested as potential biomarkers of AR disease and AR disease severity, 42–44 further emphasizing the biological relevance of our defined AR signatures.…”
Section: Resultsmentioning
confidence: 83%
“…All three of these genes have known associations with allergen‐activated type 2 inflammation, including eosinophils, type 2 cytokines, and T helper 2 (Th2) cells. Variable expression of CLC and circulating levels of MMP‐12 have been suggested as potential biomarkers of AR disease and AR disease severity, 42–44 further emphasizing the biological relevance of our defined AR signatures.…”
Section: Resultsmentioning
confidence: 83%
“… 6 The diagnostic criteria for MAR and MSAR were performed based on total nasal symptom score (TNSS) as our previous publication described, TNSS≤4 was defined as MAR, and TNSS >4 was regarded as MSAR. 17 The exclusion criteria for this study were performed as our previous study: 18 the presence of concomitant immune or inflammatory diseases, severe renal, hepatic, or cardiac dysfunction, age below 18 years, pregnancy or potential pregnancy, and history of immunotherapy or systemic steroid or anti-allergy drug use within 1 month before enrollment. HCs were excluded if they were currently undergoing immunotherapy or receiving systemic steroid or anti-allergy treatment and had severe cardiac or renal dysfunction.…”
Section: Methodsmentioning
confidence: 99%
“…The standardized Der f drops, supplied by Wolwo Pharma Biotechnology Company (Zhejiang, China), were self-administered by the AR patients as previously described. 18 The initial administration was supervised by a physician. Any adverse reactions that occurred during the therapy period were documented.…”
Section: Methodsmentioning
confidence: 99%
“…Matrix metalloproteinase-12 (MMP-12) can be induced by M2 macrophages, and promote the proliferation of Th2 cells, and secretion of IL-4 and IL-13 [ 143 ]. Zhou et al [ 144 ] found that circulating serum MRGPRX2 and MMP-12 levels were lower in the AR SLIT-treated group and useful for evaluating the disease severity.…”
Section: Predictive Biomarkers For Ait Outcomes In Allergic Diseasesmentioning
confidence: 99%